IUTAM Symposium on Multiscale Problems in Multibody System Contacts Proceedings of the IUTAM Symposium held in Stuttgart, Germany, February 20-23, 2006 - Eberhard, Peter (IUTAM Bookseries, 2007)
The investigations of multiscale problems in multibody system contacts is a most interesting and timely topic which is the subject of intensive research for more than a decade. Many questions have already been answered and the mechanically sound description and simulation is increasingly being applied to practical engineering problems. The IUTAM Symposium on "Multiscale Problems in Multibody System Contacts" in Stuttgart, Germany which was held February 20-23, 2006 facilitated discussions between researchers active in the ?eld and enabled us to review the current state of the subject, and to identify the important topics which require further e?ort. Multiscale problems occur very naturally in contact mechanics. Typically thecontactforcesandstressesareveryhighandthey aretransmittedwithina veryshortperiodoftime.This leadstoquestions,e.g.howtheslowrigidbody motion and the fast motion changes can be considered simultaneously or how interface e?ects couple with wave propagation and the large-scale motion. The purpose of the symposium was to provide a basis for discussion and exchange of new concepts and ideas between scientists from all over Europe and the world. Emphasis was placed also on sharing algorithms and concepts with young researchers who only recently entered the ?eld of mechanical c- tacts.